The Effect of Horseback Riding on Symmetry of Mechanical Properties of Muscles of Beginner and Advanced Riders with Cerebral Palsy - Laura Straubergaitė; Vilma Juodžbalienė (Lithuanian Sports University, 2019)
Research background. Since muscle activity of children with cerebral palsy is often unbalanced and this might be caused by passive mechanical properties of the muscle, it would be benefcial to analyze the properties using instrumental methods in order to evaluate the change which is induced by practicing horseback riding. Nevertheless, little literature was found on children with cerebral palsy muscle passive mechanical properties and its change while horseback The aim of the research was to evaluate and compare symmetry of mechanical properties of muscles of beginner and advanced riders with cerebral palsy while Methods. The mechanical properties of the muscles' (m. gluteus medius, m. erector spinae lumbar part) were evaluated using MYOTON-3 Results. A great difference between both body side muscle's (Gluteus medius and Erector spinae) tone asymmetry (> 10%) while standing increased. It can be explained by the fact that during the frst horseback riding exercises (which is similar to learning a new locomotor activity) a greater tension (muscle tone) is observed. Results on logarithmic gluteus medius and erector spinae muscles decrement asymmetry received after the fnal horseback riding exercise revealed that ten sessions of horseback riding is not inﬂuential enough to affect the elasticity of the mentioned muscle. The greater decrement shows depletion of mechanical energy of muscle structure. A great difference between both body sides muscle stiffness asymmetry after the tenth horseback riding exercise revealed that three-dimensional movements initiated by the horse are not inﬂuential enough in decreasing the gluteus medius and ererctor spinae muscles stiffness asymmetry for advanced and beginner horsemen. In the meantime the asymmetry of lumbar erector spinae muscle had increased for both beginners and advanced Conclusion. Ten sessions of horseback riding had not enough inﬂuence on decreasing asymmetry of gluteus medius and erector spinae muscles passive mechanical properties for both beginners and advanced riders. Keywords: horseback riding, cerebral palsy, passive mechanical properties, symmetry.